2017
DOI: 10.1002/macp.201700170
|View full text |Cite
|
Sign up to set email alerts
|

Thermal/Light Dual-Activated Shape Memory Hydrogels Composed of an Agarose/Poly(acrylamide-co-acrylic acid) Interpenetrating Network

Abstract: In this work, an agarose/poly(acrylamide‐co‐acrylic acid) interpenetrating network hydrogel is prepared by the photopolymerization of acrylamide, acrylic acid, and N,N′‐methylenebisacrylamide within agarose network at its gel state. The as‐prepared hydrogel exhibits two independent kinds of shape memory effects. The thermal‐activated shape memory behavior is attributed to the reversible coil‐helix transformation of agarose, within the permanently cross‐linked poly(acrylamide‐co‐acrylic acid) network; the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…SMHs are mainly prepared by utilizing reversible interactions, such as hydrophobic interaction, 18,19 ionic interaction, 20,21 host−guest inclusion, 22,23 hydrogen bonding, 24−26 dynamic covalent bond, 27 and coil−helix transformation. 28 Osada and co-workers 18,29 first reported the shape memory effect in hydrogels prepared by radical copolymerization of stearyl acrylate (C18) and acrylic acid (AA). The reversible order−disorder transition, i.e., the crystallization and melting of crystalline regions, associated with the hydrophobic interaction between C18 side chains endows the hydrogels with excellent shape memory properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMHs are mainly prepared by utilizing reversible interactions, such as hydrophobic interaction, 18,19 ionic interaction, 20,21 host−guest inclusion, 22,23 hydrogen bonding, 24−26 dynamic covalent bond, 27 and coil−helix transformation. 28 Osada and co-workers 18,29 first reported the shape memory effect in hydrogels prepared by radical copolymerization of stearyl acrylate (C18) and acrylic acid (AA). The reversible order−disorder transition, i.e., the crystallization and melting of crystalline regions, associated with the hydrophobic interaction between C18 side chains endows the hydrogels with excellent shape memory properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…SMHs are mainly prepared by utilizing reversible interactions, such as hydrophobic interaction, , ionic interaction, , host–guest inclusion, , hydrogen bonding, dynamic covalent bond, and coil–helix transformation . Osada and co-workers , first reported the shape memory effect in hydrogels prepared by radical copolymerization of stearyl acrylate (C18) and acrylic acid (AA).…”
Section: Introductionmentioning
confidence: 99%
“…The network structure of DN gel at each state could be found in Figure (bv). Yang et al also reported a novel thermal/light responsive agarose/poly(acrylamide‐ co ‐acrylic acid) (agarose/poly(AM‐ co ‐AAc) DN gels with controlled shape deformation. Similarly, the thermal‐activated shape deformation was controlled by the reversible sol–gel transition of agarose in the first network, while the chemically crosslinked poly(AM‐ co ‐AAc) second network served as the permanent shape [Fig.…”
Section: Shape Deformation Controlled By Both Networkmentioning
confidence: 99%
“…At present, polysaccharide polymers (chitosan, , agarose, lignin, , cellulose, ,, and guar gum , ) provide an alternative route to construct functional hydrogels for their biocompatibility, nontoxicity, low cost, and environmental friendliness. However, their applications are limited due to the monotonous function and poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%